The fire eater : poems - Hernandez Diaz, Jose (Poet) (Texas Review Press, 2020)
"'A fire eater, a man, a flame, a mime, a red house, a man in a Pink Floyd t-shirt, and a skeleton walk into a bar. They order drinks and begin a conversation about what it's like to be a character in a prose poem written by Jose Hernandez Diaz. They agree that, after a while, the internal logic makes sense, and they feel free to be themselves, to wander the landscapes of Los Angeles or the moon. They express their gratitude by promising to show up whenever Diaz needs them. Luckily, the readers of this chapbook can see the results. In Edson-esque turns of playfully absurd scenarios, Diaz reaches to the heart of our existence, and like a magician, he delights us as he confounds us. How does he do it? the audience will ask. With humor, compassion, and imagination, the three ingredients I want in any work of art."--Christopher Kennedy, Author of Clues from the Animal Kingdom TRP Chapbook Series"--